Microwave solvothermal synthesis of mixed pine tree seed-like/disc-shaped microstructures of MnOx(x = 4/3 and 1) with high specific capacitance for electrochemical capacitors - Jedsada Sodtipinta (2018)
© 2015, Springer Science+Business Media New York. The mixed pine tree seed-like/disc-shaped microstructures of MnOx(x = 4/3 and 1) were synthesized using a simple microwave-assisted solvothermal synthesis and heat treatment under N2atmosphere (heating rate 5 °C/min), without the need for carbon composite. This new mixed morphology showed high specific capacitance, as measured by the cyclic voltammetry (182 F g−1at 1 mV s−1) and by the constant galvanostatic charge-discharge cycling (195 F g−1at 0.1 A g−1). During the cycling process the specific capacitance of the material increased, which was caused by the partial electrochemical oxidation of the major phase Mn3O4(x = 4/3) to MnO2in a neutral electrolyte of 1 M Na2SO4. According to the galvanostatic charge-discharge cycling tests at 1 A g−1, this material also showed good capacitance retention for over 1000 cycles. MnOxsynthesized herein can thus be a good candidate for the electrode material for electrochemical capacitors.